The air quality perceptions of the residents of Bayview, Mossel Bay - Schoeman, J.P.; Schutte, D.W. (Clean Air Journal, 2014)
Background: In developing countries, it often occurs that little attention is given to air pollution emissions due to a lack of proper town planning, household combustion processes, energy production and the continuous growth in the transport sector (Norman et al., 2007:783). There is an increase in urban air pollution in most of the major cities of developing countries which is amplified by population growth and industrialization (World Resource Institute, 1998, 1999:1). Air pollution studies are not complete, and may fail if the quality of life and the perceptions of the studied community are not taken into consideration. This paper investigates the air quality perceptions of a high income residency surrounded by industrial activities and Mossel Bay was rated as to have potentially poor air quality by the South African Department of Environmental Affairs and Tourism. Methods: A cross-sectional survey was carried out in Bayview, Mossel Bay. The perceptions of the respondents were collected by a structured questionnaire. Components of perceptions that were tested included general opinion regarding air quality, visual perceptions of air quality, type of pollutants such as smoke and dust, perceptions regarding the source of air pollution, perceptions regarding the municipal health institution controlling air quality in Bayview, etc. These perceptions were investigated by age, gender, socio-economic status etc. Conclusion: The findings of the study indicated that various factors, such as visual impacts, type of pollutants, role of the municipal health institution governing air quality, influence the air perceptions of the Bayview residents.